The judicial control of the electoral process in Africa French speaking countries with emphasis on Senegal and Benin. - (:unkn) unknown (My University, 2018)
The election is supposed to be saving grace or redemptive moment for people. It can however suddenly become an electoral demon infringing fundamental rights due to the attitude of the political actors, the legislator or the judge in charge of arbitrating the litigations relating to it. The responsibility of the judge as a main player in the electoral process is therefore serious. People call upon him and resort to him as a last bastion. The electoral judge can foster hope or crack it down. This is the interest of the study on the judicial control of the electoral process in Africa French speaking countries with emphasis on Senegal and Benin. The analysis of the case-law relating to electoral matters reveals in this process that the judge exercises both a strict ‘regularity function’ and an electoral ‘regulation function’.The function of electoral regularity refers to the classic activity of the judge, by which he ensures that the actions of natural or legal persons, public or private, are subordinated to the electoral law. It may be before or after the election. Before the election, the regularity function includes the control of the normative and operational framework for running the election. After the election the regularity function corresponds to litigation based on the results. Extremely devoted, the post-election regularity function confers upon the judge full judicial powers of invalidation and reformation. However, the exercise of this function is retained or mitigated. The electoral judge does not relax. He designs an ingenious technique called control of sincerity which he substituted for strict electoral regularity.Furthermore, in the context of an electoral process that has been mishandled by exceptional circumstances, the judge uses an electoral regulation function based on his constitutional status as a regulator of the normal functioning of institutions and activities. Challenged with particular situations, the judge of the elec
Keywords: African Research